2010
DOI: 10.1007/s10633-010-9248-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of electroretinogram between healthy preterm and term infants

Abstract: To investigate the retinal development in healthy preterm infants through standard ganzfeld electroretinograms (ERG) and compare the difference of ERG between the healthy preterm and term infants. Forty-nine 49 healthy infants were recruited to this study, including 20 preterm and 29 term infants. All the infants were grouped as follows: term 40 W group (ERG recorded at birth), term 44 W group (ERG recorded at 4 weeks after birth), preterm 35 W group (ERG recorded at birth) and preterm 40 W group (ERG recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
1
8
0
1
Order By: Relevance
“…Healthy fullterm infants have a more immature fullfield electroretinogram (ffERG) response from rods than from cones when measured at birth indicating that cones mature earlier than rods. [3][4][5] A rapid development of the ERG response of both rods and cones takes place during the first 4 months of life, and continues slowly until early school age. 6 The ERG response in prematurely born children is very immature when recorded at 30 weeks of gestational age (GA) with low amplitudes and long implicit times for both rod and cone responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Healthy fullterm infants have a more immature fullfield electroretinogram (ffERG) response from rods than from cones when measured at birth indicating that cones mature earlier than rods. [3][4][5] A rapid development of the ERG response of both rods and cones takes place during the first 4 months of life, and continues slowly until early school age. 6 The ERG response in prematurely born children is very immature when recorded at 30 weeks of gestational age (GA) with low amplitudes and long implicit times for both rod and cone responses.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 The ERG matures continuously and in healthy preterm children tested at 40 weeks of gestation the amplitudes reach the level of fullterms tested just after birth. 4 ERG in former preterm schoolchildren has only been performed to a limited extent and mainly in children with previous retinopathy of prematurity (ROP). 9 Prematurely born children have various visual dysfunctions when tested at school age, such as decreased visual acuity (VA), affected visual fields, reduced contrast vision, and increased prevalence of refractive errors and strabismus.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that ERG reflects retinal development. In fact, changes in the ERG response during an infant’s growth reflect different developmental stages in photoreceptors, middle retinal layers and more proximal retina [ 47 ].…”
Section: Results: Critical Analysis Of Outcome Variables and Methomentioning
confidence: 99%
“…Bei ansonsten gesunden Frühchen gleichen sich die Antworten zur 40. Woche denen der gesund geborenen Kinder an [12]. Es gibt jedoch Anzeichen, dass sich die ffERG-Antworten bei Frühchen im weiteren Verlauf nicht im gleichen Ausmaß entwickeln wie bei gesunden termingeborenen Kindern und in unterschiedlichen Studien in einem bestimmten Ausmaß entweder in der Photorezeptorfunktion oder auf der Postrezeptorebene reduziert sind [13,14].…”
Section: Einfluss Der Makulareifung Auf Ganzfeld-und Multifokales Ergunclassified